Intestinal Uptake of 6(R)-L-erythro-Tetrahydrobiopterin is Distinct from the Liver-Type MTX-Sensitive Accumulation Process - Sawabe Keiko (Pteridines, 2005)
In order to increase the tissue level of tetrahydrobiopterin (BH4 ) , supplementation with 6R-tetrahydrobiopterin (6RBH4) has been widely employed. In this work, the profile of BH4 accumulation was compared between the liver and the small intestine after feeding with 10mg/kg of 6RBH4 or 7,8-dihydrobiopterin (7,8BH2 ). Endogenous BH4 was 7.20 ± 0.28 and 1.59 ± 0.13 nmol/g in the liver and the intestine, respectively. BH4 levels rose to 12.5 ± 1.35 (1.7-fold) and 53.0 + 19.6 nmol/g (40-fold) in the liver and the intestine within 30 min, respectively. Administration of 7,8BH2 caused an even higher rise in BH4 (14.4 ± 2.79 nmol/g) in the liver, while it led to a considerable increase in tissue BH2 in the intestine. When dihydrofolate reductase inhibitor MTX was administered before the pterin feeding, BH4 did not increase in the liver, while it increased 20-fold in the intestine, although the rise was 45% less than that in the absence of MTX. These results suggest that 1) the liver was scarcely able to uptake BH4 in its reduced form; 2) accumulation of BH4 in the liver was achieved through the MTX-sensitive pathway presumably driven by dihydrofolate reductase; 3) a large concentration of BH4 accumulated in the intestine, bypassing the MTX-sensitive pathway, that is, it was taken up directly as the fully reduced form, BH4 ; 4) the other BH4 accumulated in the intestine seemed to have been converted from BH2 through the MTX-sensitive pathway, as in the liver.